The Effect of Profitability, Leverage, Liquidity and Audit Committee on Islamic Social Reporting (ISR) Disclosure - Rimi Gusliana Mais; Munir Munir; Saiful Muchlis; Agita Prima Istiqorul (Indonesian Journal of Business, Accounting and Management (IJBAM), 2022)
This study aims to determine the effect of profitability, leverage, liquidity and the audit committee on the disclosure of Islamic Social Reporting (ISR) in companies listed on the Jakarta Islamic Index (JII) in 2017-2020. The population used in this study are companies listed on the Jakarta Islamic Index (JII) in 2017-2020. The sample selection in this study used purposive sampling method with the number of samples used as many as 14 companies measured using panel data regression analysis method with the help of eviews 10. Based on the results and discussion, it shows that 1) Profitability has no effect on Islamic Social Reporting (ISR) in companies listed on the Jakarta Islamic Index (JII) which is because companies are less effective in managing profits and most companies are only concerned with profit but do not report responsibility. social responsibility widely with Islamic principles, 2) Leverage has a significant positive effect on Islamic Social Reporting (ISR) on companies listed on the Jakarta Islamic Index (JII) that the size of debt has an influence on the size of the disclosure of performance and social responsibility in Islam in companies, 3) Liquidity has a significant positive effect on Islamic Social Reporting (ISR) that companies with high levels of liquidity will signal to other companies to show that a company is better than other companies. The signal is given by the company by disclosing fairly extensive information through its social responsibility report. 4) The Audit Committee has a significant positive effect on Islamic Social Reporting (ISR) on companies listed on the Jakarta Islamic Index (JII) that the number of audit committees owned by companies will have higher pressure to disclose Islamic Social Reporting (ISR) in the report company annual.